How can universities promote academic freedom? Insights from the front line of the gender wars. (18th September 2022) - Suissa, Judith; Sullivan, Alice
Abstract: The UK Government's Higher Education (Freedom of Speech) Bill is currently progressing through Parliament. The bill is designed to strengthen free speech and academic freedom in higher education, in response to what former Education Secretary Gavin Williamson describes as 'the rise of intolerance and cancel culture upon our campuses'. But is there really a crisis of academic freedom in British universities? To see that there is, say Judith Suissa and Alice Sullivan, we need only look at the contemporary reality of suppression of debate on sex and gender. The evidence they catalogue of supression of research, of blacklisting, harassment and smear campaigns, of no‐platforming, disinvitations and shutting down of events, is incontrovertible. The recent experience of scholars and students wishing to discuss the material reality and political salience of sex makes complacency about academic freedom a luxury we cannot afford. Suissa and Sullivan set out a powerful argument for the role of academic freedom in pursuing truth within the academy and developing democracy beyond it. They effectively counter attempts to narrow the scope of academic freedom so as to render it compatible with no‐platforming. And they lay out a series of practical steps administrators can take to ensure that universities are places where an expansive and pluralistic intellectual climate prevails. This is a timely and compelling intervention in a vexed but urgent public debate. For their clear‐sighted diagnosis of where and how academic freedom has been eroded in our universities, and for their judicious account of what must be done to rebuild it, Suissa and Sullivan deserve a wide and attentive hearing.